KONSEP FITRAH DAN PENDIDIKAN IDEAL - Muhammad Gus Nur Wahid; Julianne Kamilia Riza (STAI Darussalam Lampung, 2024)
The purpose of this paper is to discuss the concept of fitrah and ideal education. The research method is literature with content analysis. The results state that humans, in addition to being actors or subjects, are also objects or targets of education. Man is the raw material that will be formed according to the wishes of the educator. This human nature is carried from birth and continues to develop along with the development of human reason and in the end humans will recognize that God exists so that they will return to their God. Functionalization of Islamic education in achieving its goals is highly dependent on the extent to which the ability of Muslims to translate and realize the concept of the philosophy of human creation and the function of its creation in this universe. Islamic education is used as a conducive means for the transformation process of science and Islamic culture from one generation to the next. The position of man as khalifah and 'abd requires an educational program that offers full mastery of science in totality, so that humans are firm as khalifah and taqwa as the substance and aspect of 'abd.